Pengaruh Model Pembelajaran Inkuiri terhadap Hasil Belajar Siswa PAK-BP Siswa Kelas VIII di SMP Frater Don Bosco Tomohon - Adrianus Dalia; Fecky Evendy Singal (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
This paper is the result of quantitative research to answer the question of the influence of the inquiry learning model on the learning outcomes of PAK-BP grade VIII students at SMP Frater Don Bosco Tomohon, as well as to determine whether or not there is an influence between the inquiry learning model on student learning outcomes. This study uses a survey method which aims to determine the effect of variable X on variable Y. To find out this, calculations are used using the slovin formula so that the sample used in this study is 53. This data collection technique is made by spreading 25 items questionnaire statements and 25 test items in the form of multiple choices. As for testing data analysis using validity and reliability tests using IBM SPSS 16.0 For Windows. Based on the results of testing each variable, there is a positive and significant influence between the inquiry learning model on the PAK-BP learning outcomes of students in class VIII with a coefficient of determination of 0.445 with a percentage of 44.5% and is in the medium category with a significance level of 0.000 with an average score the average inquiry learning model of 81.55 is included in the very strong category, and the average score of PAK-BP learning outcomes for class VIII students is 79.38 included in the good category. This shows that there is an influence between the variables of the inquiry learning model on the learning outcomes of PAK-BP grade VIII students at SMP Frater Don Bosco Tomohon by contributing as much as 44.5%